Pharmacokinetic/pharmacodynamic integration of marbofloxacin after oral and intravenous administration in rainbow trout (Oncorhynchus mykiss) - Corum, Orhan; Terzi, Ertugrul; Corum, Duygu Durna; Kenanoglu, Osman Nezih; Bilen, Soner; Uney, Kamil (Elsevier BV, 2020)
Abstract The pharmaco-kinetic/dynamic of marbofloxacin was investigated after single intravenous (IV) and oral administration of 10 mg/kg in 192 healthy rainbow trout at 13 ± 1.2 °C. The plasma concentrations of marbofloxacin were determined by high-performance liquid chromatography-ultraviolet detection. After IV and oral administration, the plasma concentration–time data were described by a noncompartmental analysis. The minimal inhibitory concentration (MIC) of marbofloxacin against Yersinia ruckeri, Aeromonas hydrophila, Pseudomonas fluorescens and P. putida were determined by broth dilution method at 13 °C. After IV administration, the elimination half-life (t1/2ʎz), area under the concentration-versus time curve (AUC0-∞), apparent volume of distribution at steady-state and total body clearance of marbofloxacin were 18.05 h, 354.63 h ∗ μg/mL, 0.65 L/kg and 0.03 L/h/kg, respectively. After oral administration, t1/2ʎz, AUC0-∞, the peak plasma concentration, time of maximum concentration and bioavailability were 27.51 h, 135.29 h ∗ μg/mL, 3.74 μg/mL, 4 h and 38.15%, respectively. The respective MICs of marbofloxacin against Y. ruckeri, A. hydrophila, P. fluorescens and P. putida were determined as 0.02 μg/mL, 2.5 μg/mL, 2.5 μg/mL and 5 μg/mL, respectively. Following IV and oral administration of 10 mg/kg marbofloxacin, AUC/MIC and Cmax/MIC values were above the target levels for Y. ruckeri, while this dose was not sufficient for A. hydrophila and Pseudomonas spp. Because the pharmacokinetics and pharmacodynamics of a drug in fish are significantly affected by temperature, the dosage regimen of marbofloxacin should be modified according to temperature.
Keywords: Rainbow trout; Pharmacodynamics; Pharmacokinetics; Marbofloxacin